Role of Kruppel-like Factor 2 in Intracranial Aneurysm of the Rabbit Model - Wu, X; Zhang, J; Huang, Q; Yang, P; Chen, J; Liu, J (Cellular and Molecular Biology, 2015)
We investigated expression of Kruppel-like factor 2 (KLF2) and its correlation with basilar artery blood flow rate in the hemodynamically induced aneurysm model built by different methods. New Zealand rabbits were randomly divided into sham-operated group, unilateral ligation of common carotid artery (CCA) group (UL group) and bilateral ligation of CCA group (BL group). Rabbits were cervix-cut to expose the arteries without ligation (sham group), with right-side ligation (UL group) and bilateral ligation (BL group), respectively. Skull Doppler ultrasound was used to measure basilar artery blood flow rate in each group at week 1, 2, 3, or 4 separately (n=6 for each time point). The animals were killed after the measurements. At each time point, 6 basilar artery bifurcates from each group were collected and sent for staining (HE, EVG, Masson and KLF2 immunohistochemistry staining), while another 6 basilar artery bifurcates were processed with KLF2 Western blotting. Results showed that the average blood flow rate did not change significantly among the 4 time points in the Sham group, but it was insignificantly smaller compared to the UL group. The average blood flow rate in the BL group was significantly higher than that in the other two groups. Pathological tests showed that according to the aneurysm evaluation criteria, the basilar arteries in the Sham group had smooth tip lumina, complete endothelial cells, complete internal elastic membranes, but no fracture, thinning or aneurysm formation. Only 1 of 24 rabbits in the UL group had slight bulges in the tip of basilar artery, though not very severe. Twelve rabbits in the BL group had aneurysmal bulges, significantly different from the other two groups. KLF2 protein expression was not changed significantly with time in the Sham group, but increased slightly with time in the UL group. KLF2 protein expression in the BL group increased significantly only after 1 week and then maintained a high level, significantly different from the other two groups. KLF2 protein expression was positively correlated with blood flow rate. In conclusion, the hemodynamic change was most significant after bilateral ligation, which was most suitable for building animal models for aneurysm research. aaaAnd KLF2 expression change was consistent with blood flow rate variation, which showed positive correlation, indicating KLF2 expression was regulated by hemodynamic changes.